The English teachers’ challenges in TOEFL preparation for senior high school students - Saiful Akmal; Risdaneva Risdaneva; Habiburrahim Habiburrahim; Maulina Sari (Journal on English as a Foreign Language, 2020)
This descriptive qualitative study was aimed at discovering English language teachers’ challenges in teaching TOEFL preparation for senior high school students. The data were collected by using an in-depth interview with six experienced and qualified English language teachers teaching TOEFL in the three-state and private senior high schools in Aceh province, Indonesia. Open, axial, and selective coding techniques were used to analyze the data from in-depth interviews. The results show that teachers faced some challenges during teaching TOEFL preparation for senior high school students including students’ different language proficiency, their lack of vocabulary mastery, their fatigue, their passive attitude, class size, and time limitation. The findings recommend the further idea to organize a more organized preparation TOEFL program for high school students that can be integrated into the existing curriculum, and thus it will no longer be viewed merely as an extracurricular program.